Penerapan Teknik Artikulasi Dalam Bernyanyi Pada Paduan Suara SMA Negeri Lintong Nihuta - Neni Krisdayanti Sihite; Eben Haezarni Telaumbanua; Monang Asi Sianturi (LPPM Politeknik Pratama, 2023)
This research aims to find out singing techniques using vocal articulation in the pronunciation of words or sentences when singing in a choir so that the song lyrics can be heard clearly so that the meaning conveyed can be conveyed. This research uses a qualitative descriptive method where researchers describe in the form of speech, writing and observations in the field. The work processes carried out for data collection are: observation, documentation, observations, videos and interviews. Research is carried out by collecting information through field research to obtain results which are processed into accurate data. The results of this study indicate that the application of articulation techniques in choral singing can improve singing ability. So it is necessary to practice and master good vocal techniques to be able to sing songs well.